PENGARUH PERPUTARAN KAS DAN CURRENT RATIO (CR) TERHADAP RETURN ON ASSET (ROA) PADA PT UNILEVER INDONESIA Tbk PERIODE 2014-2023 - Maya Sintia; Yulian Bayu Ganar (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Cash Turnover and Current Ratio on Return on Assets at PT Unilever Indonesia Tbk for the period 2014-2023. The study uses a quantitative associative method. Data analysis methods include descriptive statistical analysis, classical assumption tests, multiple linear regression tests, hypothesis testing, and the coefficient of determination test, assisted by SPSS version 27. The t-test results for cash turnover on return on assets show that t-calculated <t-table, or 0.624 < 2.36426, with a significance value of 0.552 > 0.050. Therefore, it can be concluded that cash turnover does not have a significant partial effect on return on assets. The t-test results for the current ratio on return on assets show that t-calculated > t-table, or 4.158 > 2.36426, with a significance value of 0.004 < 0.050. Therefore, it can be concluded that the current ratio has a significant partial effect on return on assets. The F-test results show an F-calculated value of 10.459 > F-table 4.74, with a significance level of 0.008 < 0.05, indicating that cash turnover (X1) and current ratio (X2) simultaneously have an effect on return on assets (Y).